Resistência de genótipos de grão-de-bico (Cicer arietinum L.) a Spodoptera spp. (Lepidoptera: Noctuidae) - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Chickpea culture is the second most consumed legume in the world, and in Brazil its production is incipient, and it is necessary for the country to import large quantities that are consumed. Caterpillars of the Spodoptera complex have been reported as pests in agricultural regions of Brazilian cerrado, causing damage to several crops. The objective of this work was to evaluate the resistance of chickpea genotypes to caterpillars of the Spodoptera complex. Experiments carried out in the laboratory used the following genotypes: Jamu 96 and Blanco Sinaloa 92 (Mexico); National 29 (Cuba); BG 1392 (Spain), Kalifa, BRS Cristalino, FLIP 02- 23C, BRS Toro, National 27, 004UP, 003UP, BRS Cicero, BRS Aleppo. It was evaluated the attractiveness in a test with chance and no chance of choice for feeding with 3rd instar caterpillars, determining the number of larvae attracted by genotype at different times and the index of preference, antibiosis and nutritional indexes of Spodoptera frugiperda caterpillars in genotypes of chickpeas. The Kalifa and Nacional 27 genotypes were more attractive to Spodoptera cosmioides in the choice of attractiveness test, and in the test with no chance of choice significant differences were observed only at the fifteen minute and two hour times. The most preferred genotypes for feeding were BG 1392, Jamu 96, 004UP, Nacional 29, BRS Cicero, BRS Toro, 003UP and FLIP 02-23C, these indicate the presence of repellent stimuli and deterrents to S. eridania feeding. The less preferred genotypes were Jamu 96, BRS Cicero, BRS Toro, BRS Aleppo and FLIP 02-23C, which lower preference may be associated with the mechanism of antixenosis. The genotypes BG 1392, Blanco Sinaloa 92, Jamu 96, BRS Cristalino, 004UP, Kalifa, BRS Cicero, BRS Toro, BRS Aleppo, 003UP and FLIP 02- 23C extended the larval period of S. frugiperda in relation to National 29 and National 27 It is necessary to seek alternative methods in the control of insect pests, aiming at a sustainable agriculture. The genotypes National 29, BRS Cicero, BRS Toro and 003UP have resistance of the type antixenose to S. eridania. The genotypes Jamu 96, BRS Cristalino, BRS Cicero, BRS Toro, BRS Aleppo, 003UP and FLIP 02-23C have resistance of antixenose type to S. frugiperda. The genotypes Nacional 29, Nacional 27 and BRS Cicero show antibiosis resistance to S. frugiperda. There are few studies related to resistance of Spodoptera spp. the cultivation of chickpeas, being possible with this work to offer results to the producers.
Keywords: Resistência de plantas a insetos; antibiose; não-preferência; leguminosas; Resistance of plants to insects; antibiosis; non-preference; legum; CIENCIAS AGRARIAS